KOMBINASI FEEDING BIOSTARTER DAN AIR DALAM ANAEROBIK DIGESTER - Budihardjo, Mochamad Arief (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2009)
The research was conducted to investigate how much biostarter and water adding influence to biogas which is produced from organic waste degradation process of market and restaurant organic waste by anaerobic process. In this research, biostarter acts as catalyst to quicken organic waste degradation process while water addition function as moisturizer substrates factor in digester. Contribution of biostarter and water combination addition, be able to yield a lot of biogas which contains methane gas is significant. Research was set as laboratory scale experiment using batch system with fifth variations of treatment observed. The variations aim to determine a most effective variation which has capabilities to yield a lot of volume biogas, methane gas and the high efficiency of quality slurry reduction on a brief HRT (Hydraulic Retention Time). The result of theÂ  research indicates that methane gas percentage in biogas at every variant range from 21.89 - 30.78 %, acid substrate level 5.47 - 7.41, which still at a preferable range for bacteria to live and efficiency of slurry quality reduction at every variant especially at its organic content range from 15.29 - 93.92 %